Draft Five Year Plan 1978-83 Welfare of Scheduled Castes and Scheduled Tribes Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
According to 1971 census after removal of the area restrictions, the tribal population has increased from 83.87 lakhs to 98.15 lakhs representing 23.56% of the total population of the State. Out of 442481 Sq.Kms. area of the State, 161022 Sq.Kms. forming 36% of the total area falls in tribal areas. In 45 Districts of the State, 174 Blocks of 21 Districts have more than 60% of the total tribal population. There are 58 tribal communities of which 13 are more-backward and out of them 5 are classified as primitive groups.
Government of Madhya Pradesh, Planning, Economics and Statistics Department